IDENTIFIKASI REVITALISASI PERKEBUNAN KELAPA SAWIT DI SUMATERA UTARA - Juliza Hidayati, Sukardi, Ani Suryani, Anas Miftah Fauzi, Sugiharto (Jurnal Teknologi Industri Pertanian, 2016)
Since 2006, Indonesia’s CPO production has surpassed Malaysia’s to be the world largest producer.Nevertheless, Indonesia is evidently lower in productivity. The expectation for new plantation is relatively highdue to the constant increasing demand for CPO, especially for biodiesel related purposes. North Sumateraprovince as the pioneer in palm oil plantation in Indonesia has huge potentials to grow in the future, with theexisting plantation land of 12.71% out of total plantation land in Indonesia. The idea of setting up NorthSumatera as a benchmark in national palm plantation industry is not impossible. For that reason, the plantationrevitalization program should be carried out. The aim of palm oil plantation revitalization program is toincrease competitiveness mainly by increasing productivity. This can be achieved not only through plantationland extent but also by increasing the land productivity per hectare. Hence, it is crucial that the process toidentify all possible efforts in order to increase palm oil plantation productivity in North Sumatera be carriedout. Identification process might start by analyzing all factors affecting palm oil plantation productivity by usinganalytical network process (ANP). Potential factors that have huge impact to increasing land productivity aresuch as plant diseases, seeding, fertilizer selection, fertilizer dosage, appropriate tools and equipment used, typeof land, fertilizing frequency, working procedures, weeding control, pest control, fertilizing technology and seedfertilizing. Population per hectare and plant uniformity up to 31.5%, and fertilizing at 27.6% would contributeas the main factors to be closely monitored and observed further in order to increase palm oil plantationproductivity.Keywords: Palm oil agroindustry, plantation revitalization, productivity, the pioneer in palm oil plantation